The Effect of Disaster Management Training with Simulation Method on Flood Disaster Preparedness Behavior in SMAN 2 Tuban Students - Lukman Hakim; Mei Widyawati (Alliance oh Health Activists (AloHA), 2021)
Indonesia is a disaster-prone area, not only natural disasters but also non-natural disasters. Students are one of the nation's assets that are prone to disasters and there is no preparedness in dealing with disasters. However, based on the experiences of students from PMR and SATGAS KESDA member organizations, it shows that there has been no learning of disaster simulation training. The purpose of this study was to determine the effect of disaster management training with the simulation method on flood disaster preparedness behavior in SMAN 2 Tuban students. The research method used is pre-experimental, with a one-group pre-post-test design. The research sample was 28 students who were members of the PMR and SATGAS KESDA member organizations which were selected by simple random sampling. Disaster Simulation SOP research instrument and preparedness behavior questionnaire sheet. The results showed that most of the students' preparedness behavior in dealing with flood disasters before being given disaster management training with the simulation method was categorized as unprepared behavior, and after being given disaster management training with the simulation method most of them were categorized as ready behavior. The results of the statistical test showed that there was an effect of disaster management training using the simulation method on flood preparedness behavior in SMAN 2 Tuban students with p value = 0.001 at =0.05 (p